Comparative metagenomic analysis on COPD and health control samples reveals taxonomic and functional motifs - Chen, Guangyi; Wiegand, Chantal; Willett, Andreas; Herr, Christian; Müller, Rolf; Bals, Robert; Kalinina, Olga V. (Frontiers in Microbiology, 2025)
Chronic obstructive pulmonary disease (COPD) is a progressive lung condition marked by persistent respiratory symptoms and airflow limitation and significantly affects global health. The intricate relationship between COPD and the lung microbiome has garnered attention, with metagenomic analyses revealing critical insights into microbial community dynamics and their functional roles. In this study, we conducted a comprehensive metagenomic analysis comparing throat samples from COPD patients (n = 26) and healthy controls (n = 32) derived from a large cohort analyzed at the Saarland University Hospital. Taxonomic profiling and differential abundance analysis indicated a significant reduction of the microbial diversity in COPD patients, with notable overrepresentation of pathogenic bacteria, such as Veillonella parvula (NCBI:txid29466), Streptococcus gordonii (NCBI:txid1302), Scardovia wiggsiae (NCBI:txid230143), as well as a less stable microbiome composition than in healthy individuals. Functional profiling identified alterations in metabolic pathways implicating microbial dysbiosis in disease progression. The study also highlighted enrichment of inflammation-related pathways in COPD samples, emphasizing the microbiome’s role in inflammatory processes. Comparative analysis of bronchoalveolar lavage (BAL) and throat samples collected from the same 11 individuals further underscored distinct microbial compositions across respiratory tract regions, suggesting spatial variability in microbial communities. Metagenomic approaches including analysis of metabolic pathways showed significant alteration of the microbiome of the lung in COPD.